(untitled) (European Journal of Pure and Applied Mathematics, 2023)
In this paper, the divisibility property of the type 2 (p,q)-analogue of the r-Whitney numbers of the second kind is established. More precisely, a congruence relation modulo pq for this (p,q)-analogue is derived.